Establishment of three heterogeneous subtypes and a risk model of low-grade gliomas based on cell senescence-related genes - Chen, Jing; Wu, Lingjiao; Yang, Hanjin; Zhang, XiaoChen; Xv, SuZhen; Qian, Qiong (Frontiers in Immunology, 2022)
Background: Cellular senescence is a key element in the occurrence and progression of a variety of tumors. As a result, cellular senescence-related markers can be categorized based on the prognosis status of patients. Due to the heterogeneity and the complexity of the tumor microenvironment (TME), the long-term effectiveness of low-grade glioma (LGG) treatment remains a clinical challenge. Consequently, developing and refining effective treatment approaches to aid with LGG management is critical. Methods: Based on the expressions of cell senescence-related genes (CSRGs) acquired from the cellAge database, consensus clustering was utilized to identify stable molecular subtypes. Clinical features, immune infiltration, route modifications, and genetic changes of various subtypes were also assessed. Following that, the least absolute shrinkage and selection operator (LASSO) regression and univariate Cox regression analysis were used for developing the cell senescence-related risk score (CSRS) model. Finally, a correlation study of the CSRS model with molecular, immunological, and immunotherapy parameters was performed. Results: C1, C2, and C3, are the three senescence-related subtypes that were identified. Patients belonging to the C1 subtype had poor prognoses and a substantial proportion of them was in the grade G3. The differentially expressed genes (DEGs) among the three subtypes were used to develop the CSRS model. In both the training and independent validation cohort, the model had a high area under the receiver operating characteristic (ROC) curve in predicting the overall survival (OS) of patients. As a result, this model can predict clinical features and responses to immunotherapy in a variety of patients and it is a potential independent prognostic factor for LGG. Conclusion: This research discovered three LGG subtypes related to cell senescence and created a CSRS model for six genes. Cell senescence was highly associated with unfavorable prognosis in LGG. The CSRS model can be used to predict the prognosis of patients and identify patients who would benefit from immunotherapy.